Immune aging in multiple sclerosis is characterized by abnormal CD4 T cell activation and increased frequencies of cytotoxic CD4 T cells with advancing age - Zuroff, Leah; Rezk, Ayman; Shinoda, Koji; Espinoza, Diego A.; Elyahu, Yehezqel; Zhang, Bo; Chen, Andrew A.; Shinohara, Russell T.; Jacobs, Dina; Alcalay, Roy N.; Tropea, Thomas F.; Chen-Plotkin, Alice; et al. (EBioMedicine, 2022)
Immunosenescence (ISC) describes age-related changes in immune-system composition and function. Multiple sclerosis (MS) is a lifelong inflammatory condition involving effector and regulatory T-cell imbalance, yet little is known about T-cell ISC in MS. We examined age-associated changes in circulating T cells in MS compared to normal controls (NC). Forty untreated MS (Mean Age 43·3, Range 18–72) and 49 NC (Mean Age 48·6, Range 20–84) without inflammatory conditions were included in cross-sectional design. T-cell subsets were phenotypically and functionally characterized using validated multiparametric flow cytometry. Their aging trajectories, and differences between MS and NC, were determined using linear mixed-effects models. MS patients demonstrated early and persistent redistribution of naïve and memory CD4 T-cell compartments. While most CD4 and CD8 T-cell aging trajectories were similar between groups, MS patients exhibited abnormal age-associated increases of activated (HLA-DR+CD38+; (P = 0·013) and cytotoxic CD4 T cells, particularly in patients >60 (EOMES: P < 0·001). Aging MS patients also failed to upregulate CTLA-4 expression on both CD4 (P = 0·014) and CD8 (P = 0·009) T cells, coupled with abnormal age-associated increases in frequencies of B cells expressing costimulatory molecules. While many aspects of T-cell aging in MS are conserved, the older MS patients harbour abnormally increased frequencies of CD4 T cells with activated and cytotoxic effector profiles. Age-related decreased expression of T-cell co-inhibitory receptor CTLA-4, and increased B-cell costimulatory molecule expression, may provide a mechanism that drives aberrant activation of effector CD4 T cells that have been implicated in progressive disease. Stated in Acknowledgements section of manuscript.